High-stability cqds modified cu-based catalysts, preparation and application thereof
Patent Information
- Application Number
- CN202510642271.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-19
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-05-19
AI Technical Summary
[0005]目前,现有技术中没有采用碳量子点的电子储存性能避免Cu+的还原,维持Cu+的长期稳定性的相关报道,也没有相关的技术启示
[0018](1)本发明开创性地提出了一种具备高稳定性的CQDs改性Cu基催化剂。所述CQDs改性Cu基催化剂采用碳量子点的电子储存性能避免Cu+的还原,实现了Cu+的长期稳定性,产生了意料不到技术效果。
Smart Images

Figure CN120485843B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical technology and relates to a highly stable Cu-based catalyst, specifically a CQDs-modified Cu-based catalyst, its preparation, and its application in electrochemical reactions. Background Technology
[0002] Copper (Cu)-based catalysts play a crucial role in electrochemical reactions due to their unique electronic structure and tunable oxidation state (Cu). 0 / Cu + / Cu 2+ Cu, with its cost advantages, is widely used in various key electrocatalytic processes. Among them, in the CO2 reduction reaction, Cu... + Cu is a key active species in C2 products, accelerating the activation of inert CO2 molecules and significantly reducing the CC coupling barrier. In the electroreduction of nitrates, Cu-based catalysts (such as Cu2O) can efficiently reduce nitrates (NO3-) in water to ammonia (NH3) or nitrogen (N2), solving water pollution problems. In the oxygen reduction reaction (ORR), Cu-NC single-atom catalysts (Cu-N4 sites) exhibit ORR activity close to that of Pt, and at a lower cost. However, due to the high overpotential required in practical operation, the applied potential is often significantly higher than that of Cu. + / Cu 0 Reduction potential, leading to Cu + It is inevitably reduced to Cu during the reaction process. 0 This leads to a decrease in performance. Therefore, how to maintain Cu under high overpotential conditions is a key issue. + The stable existence of Cu is one of the key challenges in improving the performance of Cu-based catalysts.
[0003] To stabilize Cu + To modify Cu species, various strategies have been employed, including heteroatom doping, metastable state construction, defect engineering, interface engineering, and heterojunction construction, with the aim of altering the coordination environment to modulate the electronic structure of Cu species. However, catalysts modified by these methods are prone to structural deterioration and may be limited by excessively low current densities and narrow potential windows. Especially under conditions of insufficient CO2 gas feed or at more negative reduction potentials, catalyst remodeling is inevitable, leading to Cu degradation. + The loss of stability reduces the selectivity of C2 products. Therefore, how to maintain Cu stability in harsh reducing environments is a key challenge. + The long-term stability of [the substance] is a technical problem that urgently needs to be solved in electrochemical reactions.
[0004] Carbon quantum dots (CQDs), as unique nanomaterials, exhibit a discrete energy level structure due to their quantum size effect. Their lowest unoccupied molecular orbital (LUMO) energy levels are relatively low and can be adjusted through chemical modification or physical manipulation. When the energy of an external electron is higher than the LUMO level of the CQD, the electron will spontaneously transfer into the CQD. Furthermore, CQDs typically possess a highly delocalized π-electron system. This structural characteristic not only contributes to the dispersion and stabilization of electrons but also endows CQDs with efficient electron accepting and transferring capabilities, thus enabling them to possess excellent electron storage performance. Based on these characteristics, carbon quantum dots are currently widely used in energy storage and conversion. When used as electrode materials in supercapacitors, CQDs' high specific surface area and delocalized π-electron system accelerate charge adsorption / desorption, achieving high energy density (>200 F / g) and long cycle stability (>10,000 cycles). In lithium / sodium-ion batteries, CQDs can serve as anode materials to alleviate volume expansion and as conductive additives to reduce interfacial impedance, thereby improving battery rate performance (>5C) and cycle life. Furthermore, by modulating the LUMO energy level and light absorption characteristics, CQDs can promote electron transfer efficiency in photocatalytic water splitting, achieving hydrogen production rates on the order of μmol·h⁻¹·g⁻¹. Flexible modification of surface functional groups can also anchor active sites, further synergistically optimizing electrochemical and photoelectric energy conversion processes, providing innovative pathways for the development of clean energy technologies.
[0005] Currently, no existing technology utilizes carbon quantum dots to avoid the electronic storage performance limitations of Cu. + The reduction of Cu + There are no reports on its long-term stability, nor are there any related technical insights. Summary of the Invention
[0006] Therefore, this invention innovatively proposes a highly stable CQDs-modified Cu-based catalyst. The CQDs-modified Cu-based catalyst utilizes the electron storage properties of carbon quantum dots to avoid Cu... + The reduction of Cu was achieved + The application also provides the long-term stability of the CQDs-modified Cu-based catalyst. Furthermore, this application provides a method for efficiently performing electrochemical reactions using the aforementioned CQDs-modified Cu-based catalyst. By adjusting the appropriate pulse time and pulse potential, the electron storage and release cycle of CQDs is achieved, fundamentally solving the technical problem of the limited electron storage capacity of CQDs.
[0007] The technical solution of the present invention:
[0008] A highly stable CQDs-modified Cu-based catalyst is disclosed. The modified copper-based catalyst comprises a copper-based catalyst and an appropriate amount of CQDs dispersed on the surface of the copper-based catalyst, wherein the weight ratio of the copper-based catalyst to the CQDs is 100:2-100:20. The copper-based catalyst is Cu... 2-x Se, CuO, Cu2O, CuS, Cu2S, or Cu3N.
[0009] The applicant unexpectedly discovered that adding a small amount of CQDs during the hydrothermal synthesis of Cu-based catalysts significantly enhances their catalytic activity. The inventors, through analysis, believe this is based on the electron storage properties of carbon quantum dots. + The reduction of species is essentially driven by an electron transfer process from the cathode to the catalyst surface. From a thermodynamic perspective, the energy is higher than that of Cu. + / Cu 0 Electrons at the reduction potential can be reduced by Cu + Spontaneous capture, thus causing Cu + To Cu 0 The reduction process. In CQDs-modified Cu-based catalysts, the applicant discovered that the LUMO energy level of CQDs is slightly lower than that of Cu. + / Cu 0 The potential, through precise energy level matching, enables CQDs to act as an electron storage pool, preventing excess unreacted electrons from igniting the active Cu. + Reduced to less reactive Cu 0 —By storing the electrons originally intended to lower the oxidation state of Cu in a π-electron conjugated structure, Cu avoids… + The reduction of Cu was achieved + The long-term stability of the Cu-based catalyst is achieved. In other words, the CQDs-modified Cu-based catalyst effectively resists catalyst reconstruction by switching electrons along thermodynamically preferential reaction pathways, thereby achieving Cu... + Long-term stability of species.
[0010] The preparation method of the CQDs-modified Cu-based catalyst as described above includes the following steps: CQDs and the raw materials for preparing the copper-based catalyst are added to a reaction apparatus, and the reaction is completed using a hydrothermal synthesis method to obtain the CQDs-modified Cu-based catalyst. The hydrothermal synthesis conditions are 160-200℃ for 18-30 hours.
[0011] The previously described application of CQDs-modified Cu-based catalysts in electrochemical reactions. Specifically, these catalysts are used as electrodes in electrochemical reactions with reduction potentials exceeding -0.37 V vs. RHE. Simultaneously, the CQDs-modified Cu-based catalysts also function as catalysts in these electrochemical reactions.
[0012] Preferably, the electrochemical reaction is specifically CO2 reduction, HER, OER, ORR, N2 reduction, or NO3 reduction. - reduction.
[0013] However, electroreduction reactions are usually carried out by continuous electrolysis at harsh reduction potentials to achieve long-term reactions, while the electron storage capacity of CQDs is limited. Therefore, the aforementioned CQDs-modified Cu-based catalysts have improved the stability of Cu-based catalysts to some extent, but have not fundamentally solved the problem.
[0014] Based on this, the present invention also provides a method for efficiently carrying out electrochemical reactions using CQDs-modified Cu-based catalysts as described above, specifically using pulse electrolysis. The inventors unexpectedly discovered that by adjusting the appropriate pulse time and pulse potential, the aforementioned technical problems were effectively solved using pulse electrolysis, achieving high stability of the CQDs-modified Cu-based catalyst. The inventors speculate that this is because, by applying an oxidation pulse potential, the electrons stored in the CQDs are released and converted into "active electrons," thereby overcoming the limitation of their electron storage capacity. In other words, combining the electron storage of CQDs with pulse electrolysis achieves the periodic storage and release of electrons, forming a reversible energy storage cycle similar to charging and discharging. Therefore, this method fully utilizes the electron storage and release capabilities of carbon quantum dots, effectively avoiding Cu… + Reduced to Cu by too many electrons 0 This approach fundamentally achieves high stability of CQDs-modified Cu-based catalysts, not only representing a significant improvement in technical performance compared to existing technologies, but also solving the aforementioned technical problems in the application of CQDs-modified Cu-based catalysts in electrochemical reactions.
[0015] The pulse potential of the pulse electrolysis is 0.2–0.8 V vs. RHE, and the pulse duration is 2–10 s. Using the aforementioned pulse electrolysis parameters to electrocatalyze the reduction of CO2 to prepare C2 products significantly improves the selectivity and reaction efficiency of the C2 products. By applying a low pulse potential and precisely controlling the pulse electrolysis parameters to switch the electrode reaction path and release electrons stored in CQDs, the electron storage capacity limitation of CQDs is overcome, thereby realizing Cu… + The method achieves long-term stability. Therefore, under the aforementioned pulsed electrolysis conditions, the method optimizes the utilization of the electron storage and release capabilities of carbon quantum dots, thereby significantly improving the selectivity and reaction efficiency of CO2 electrocatalytic reduction to C2 products, and providing a new technical path for achieving efficient and green CO2 conversion.
[0016] Preferably, the potential of the pulse electrolysis is 0.4–0.6 V vs. RHE, and the pulse duration is 4–8 s.
[0017] The beneficial effects of this invention are:
[0018] (1) This invention innovatively proposes a CQDs-modified Cu-based catalyst with high stability. The CQDs-modified Cu-based catalyst utilizes the electronic storage properties of carbon quantum dots to avoid Cu... + The reduction of Cu was achieved + Its long-term stability has produced unexpected technical effects.
[0019] (2) This application provides a method for efficient electrochemical reaction using Cu-based catalysts modified with CQDs as described above. By adjusting the appropriate pulse time and pulse potential, the electron storage and release cycle of CQDs is realized, which fundamentally solves the technical problem of the limited electron storage capacity of CQDs.
[0020] (3) The method described in this invention significantly improves the selectivity and reaction efficiency of CO2 electrocatalytic reduction to C2 products, providing a new technical path for achieving efficient and green CO2 conversion. Attached Figure Description
[0021] Appendix Figure 1 This is a diagram illustrating the strategy mechanism based on energy level matching.
[0022] Appendix Figure 2 Cu prepared in Example 1 2-x TEM image of Se / CQD;
[0023] Appendix Figure 3 Cu in Example 2 2-x Se / CQD, Cu 2-x Cyclic voltammetry curves of Se and CQDs;
[0024] Appendix Figure 4 Cu under pulsed electrolysis in Example 3 2-x In-situ XRD of Se / CQD;
[0025] Appendix Figure 5 Cu in Example 3 2-x In-situ Raman spectra of Se / CQD under constant / pulse potential.
[0026] Appendix Figure 6 Cu under constant potential and pulsed electrolysis conditions in Example 4 2-x Se and Cu 2-x Performance of Se / CQD in CO2 electroreduction reaction. Detailed Implementation
[0027] The present invention will be further described below with reference to the embodiments.
[0028] Example 1: Preparation of CQDs-modified copper-based catalyst
[0029] (1) Preparation of CQDs by hydrothermal synthesis of citric acid
[0030] Several methods for preparing CQDs have been publicly reported in the prior art. This embodiment uses a hydrothermal synthesis method with citric acid to prepare CQDs. Specifically, citric acid (1.751 g) and ethylenediamine (558.3 μL) are dissolved in an appropriate amount of deionized water (16.67 mL). The solution is then transferred to a polytetrafluoroethylene-lined autoclave and heated at 180-200 °C for 3-5 hours. After the reaction is complete, the mixture is naturally cooled to room temperature to obtain a brownish-black, transparent product, which is then dialyzed and lyophilized to obtain the CQDs.
[0031] (2) Preparation of CQDs-modified Cu-based catalysts
[0032] The aforementioned CQDs and the raw materials for preparing the copper-based catalyst were added to a reaction apparatus, and the reaction was carried out using a hydrothermal synthesis method to obtain the CQDs-modified Cu-based catalyst. Specific Cu-based catalysts, reaction conditions, and corresponding products are detailed in Table 1.
[0033] Table 1. Conditions and corresponding products for the hydrothermal synthesis of CQDs-modified Cu-based catalysts
[0034] reaction temperature 180℃ 200℃ 160℃ 200℃ 160℃ 200℃ reaction time 24h 30h 18h 30h 18h 30h weight ratio 100:6 100:2 100:20 100:2 100:20 100:12 product <![CDATA[Cu 2-x Se / CQD]]> CuO / CQD <![CDATA[Cu2O / CQD]]> CuS / CQD <![CDATA[Cu2S / CQD]]> <![CDATA[Cu3N / CQD]]>
[0035] Note: (1) The weight ratio refers to the weight ratio of copper-based catalysts to CQDs.
[0036] Given that the preparation methods of the Cu-based catalysts have all been disclosed in the prior art, this embodiment only uses Cu... 2- x Taking Se / CQD as an example, Cu 2-x The specific preparation steps for Se / CQD are as follows: 0.2 g of copper acetate monohydrate (Cu(CH3COO)2·H2O) was dissolved in 20 ml of diethylenetriamine (DETA), and the solution gradually turned blue. 10 ml of deionized water containing 6 mg of CQDs was added under stirring. Then, the mixture was stirred continuously at room temperature for 20 minutes, and 1.0 mmol (0.173 g) of sodium selenite (Na2SeO3) was added to the solution. Subsequently, the resulting mixed solution was placed in a sealed container and reacted at 180 °C for 24 hours. After precipitation, centrifugation, washing, and freeze-drying, Cu was obtained. 2-x Se / CQD. Cu 2-x In Se / CQD, Cu 2-x The weight ratio of Se to CQDs is 100:6.
[0037] The CQDs-modified copper-based catalysts prepared above were characterized using TEM, and the results were similar. Now, Cu... 2-x Let's take Se / CQD as an example for explanation. 2-x For details on the morphological structure of Se / CQD, please refer to Figure 2 , Figure 2 The scale bar for a-2d decreases from 200 nm to 10 nm, thereby gradually magnifying the morphology and structure. For example... Figure 2 As shown in a-2d, Cu 2-x The uniform distribution of CQDs on the surface of the Se material indicates that the CQDs-modified copper-based catalyst was successfully prepared in this embodiment.
[0038] Example 2: Determination of redox potential of Cu-based catalyst, CQDs-modified Cu-based catalyst, and CQDs
[0039] The redox potentials of the Cu-based catalyst, the CQDs-modified Cu-based catalyst, and the CQDs described in Example 1 were detected by cyclic voltammetry.
[0040] The specific method is as follows: Electrochemical measurements were performed using a conventional three-electrode system. The material was coated onto a glassy carbon electrode and polished with an alumina slurry (0.3 mm), followed by ultrasonic treatment in ethanol. A 2 μl catalyst suspension was coated onto the glassy carbon electrode surface, and tests were conducted in a dimethylformamide (DMF) solution containing 0.1 M tetrabutylammonium tetrafluoroborate ((Bu)4NBF4), with a voltage range of -1.6–0.6 V vs. Ag / AgCl and a scan rate of 200 mV s. -1 The results are detailed in Table 2-3.
[0041] Table 2. Cyclic voltammetry results of Cu-based catalysts
[0042]
[0043] As shown in Table 2, the copper-based catalyst (Cu) 2-x Se, CuO, Cu2O, CuS, Cu2S or Cu3N)Cu + / Cu 0 The reduction potentials of Ag and AgCl are -0.91 to -0.95 V, which are relatively close to each other.
[0044] Table 3. Redox potentials of CQDs-modified Cu-based catalysts
[0045]
[0046] Table 3 shows that CQDs modified Cu-based catalysts (Cu 2-xIn the CQDs modified Cu-based catalysts (Se / CQD, CuO / CQD, Cu2O / CQD, CuS / CQD, Cu2S / CQD, or Cu3N / CQD), Cu is a type of catalyst with CQDs. + / Cu 0 The reduction potentials of Cu are -0.81 to -0.85 V vs. Ag / AgCl, which are relatively close to each other. Meanwhile, the storage potential of CQDs is -0.80 V vs. Ag / AgCl. This indicates that in Cu-based catalysts modified with CQDs, the electrons originally used to reduce the oxidation state of Cu are stored in the π-electron conjugated structure of the CQDs due to the presence of CQDs. Therefore, in Table 3, Cu... + →Cu 0 The reduction potential is actually the storage potential of CQDs. This also fully demonstrates that, compared with the aforementioned Cu-based catalysts, CQDs-modified Cu-based catalysts all exhibit CV characteristic signals consistent with CQDs.
[0047] The following uses Cu 2-x Se, Cu 2-x Taking Se / CQD and CQDs as examples, a specific explanation will be given. First, Cu is processed in a DMF electrolyte dissolved in 0.1M (Bu)4NBF4. 2-x Se, Cu 2-x CV tests were performed on Se / CQD and CQDs. See details for the results. Figure 3 .like Figure 3 As shown, pure Cu 2-x Se exhibits two typical redox pairs, corresponding to Cu + / Cu 0 and Cu 2+ / Cu + The redox potential of Cu + The reduction potential of Cu is -0.91V vs. Ag / AgCl (i.e. -0.37V vs. RHE). 2-x Se of Cu 0 The area of the oxidation peak is significantly smaller than that of Cu. + The reduction peak area indicates that Cu + / Cu 0 The redox reaction of Cu is irreversible. + Reduced to Cu 0 It is difficult to return to Cu through electrochemical oxidation. + CQDs exhibit significant electron absorption and release peaks, indicating their excellent electron storage and release capabilities; and their absorption peak position (-0.80V vs. Ag / AgCl) is slightly lower than that of Cu. + / Cu 0 The reduction potential of Cu, this thermodynamic advantage proves that it can be used to store the original Cu.+ Electrons to protect Cu + More importantly, Cu 2-x Se / CQDs exhibit a similar CV signal to CQDs, further demonstrating that CQDs protect Cu through their excellent electronic storage properties. + .
[0048] Example 3: Pulse electrolysis to maintain Cu 2-x Cu in Se / CQD catalyst + Stability Study
[0049] In this embodiment, in-situ XRD and in-situ Raman spectroscopy were used to determine the evolution of the Cu valence state in the CQDs-modified Cu-based catalyst under pulsed electrolysis (pulse parameters are detailed in Table 4), and the results were consistent. Now, Cu... 2-x The results of Se / CQD with a pulse potential of 0.6V vs. RHE and a pulse duration of 5.0s will be used as an example to illustrate the specific results.
[0050] Table 4. Maintaining Cu 2-x Cu in Se / CQD catalyst + Stability of pulse parameters
[0051] Pulse potential / V vs. RHE 0.2 0.4 0.6 0.8 Pulse time / s 2.0 8.0 5.0 10.0
[0052] For detailed in-situ XRD results, please refer to Figure 4 .like Figure 4 As shown, due to Cu 2-x Thermodynamic instability of Se, Cu 2-x Se / CQD is first rapidly reconstituted under pulsed electrolysis to form a mixed phase of Cu₂Se (PDF#04-0839) and CuSe (PDF#27-0184) rich in high-oxidation-state Cu sites. More importantly, the Cu sites can remain stable under strong reducing conditions, avoiding the degradation of highly oxidized Cu. + / Cu 2+ Cu is generated by high-potential electron attack at the site. 0 Therefore, the reversible cyclic process, composed of the electron storage characteristics of CQDs and the electron coupling of pulsed electrolytic discharge, can effectively maintain the highly active oxidation state of Cu, thus exhibiting high C2 product selectivity.
[0053] For detailed results of in-situ Raman testing, please refer to Figure 5 .like Figure 5 As shown, Cu 2-x Under constant potential, the Cu-Se bond signal disappears within tens of seconds, indicating that its Cu... + The variety decreased rapidly. (Cu) 2-x Se / CQD can significantly prolong the Cu-Se bond signal intensity, indicating that the electron storage solution of CQDs can protect Cu.+ However, due to the limited storage capacity of CQDs, the overflowing electrons will continue to reduce Cu. + Quantity. Subsequently, the electrolysis conditions were changed from constant potential to pulsed potential. Under pulsed potential, the initial Cu... 2-x The Se bond signal peak can maintain its intensity for a certain period of time, but the peak gradually broadens and eventually disappears. This indicates that under pulsed oxidation potential, Cu... 2-x Cu in Se + Species can be partially derived from Cu 0 Oxidized to Cu + But Cu 2-x The structure of Se ultimately results from the irreversible Cu... + / Cu 0 Redox reactions are destroyed. This indicates that Cu only thrives when both the CQD load and the pulsed conditions (pulse potential of 0.2–0.8 V vs. RHE, pulse duration of 2–10 s) are simultaneously satisfied. 2-x Only Se / CQD can achieve Cu + Its long-term stability.
[0054] Example 4: Application of CQDs-modified Cu-based catalysts in CO2 electroreduction reaction
[0055] Based on the results of Examples 1-3, the inventors believe that CQDs-modified Cu-based catalysts can be used as electrodes for electrochemical reactions, wherein the reduction potential of the electrochemical reaction exceeds that of Cu. + / Cu 0 The redox potential can be determined. Figure 3 It can be seen that Cu + / Cu 0 The reduction potential of Cu is -0.91V vs. Ag / AgCl. According to the formula E(RHE)=E(Ag / AgCl)+0.0591pH+0.197, the reduction potential of Cu is... + / Cu 0 The reduction potential is -0.37V vs. RHE. The electrochemical reactions mentioned include, but are not limited to, CO2 reduction, HER, OER, ORR, N2 reduction, or NO3 reduction. - Reduction. The applied potentials of these electrochemical reactions all exceed -0.37V vs. RHE, inevitably leading to Cu reduction. + The reduction of species leads to a decrease in catalytic activity.
[0056] The following detailed explanation uses CO2 reduction as an example. Electrochemical measurements were performed in a flow cell, with a gas diffusion electrode as the working electrode, Ni foam as the counter electrode, and Hg / HgO as the reference electrode. The cathodic and anodic electrolytic cells were separated by a Nafion 117 proton exchange membrane. Both the cathode and anode electrolytes were 1.0M potassium hydroxide solutions, and a peristaltic pump was used to circulate the liquid phase. CO2 gas was introduced as a reactant, and its flow rate was controlled by a mass flow meter. Both the working and counter electrodes were fixed with conductive copper strips. The CO2ER experiment was conducted for 15 minutes at different application potentials to obtain relatively stable and reliable performance parameters, followed by quantitative analysis. Cu... 2-x Se, Cu 2-x CO2 electroreduction experiments were conducted using Se / CQD under constant potential and pulsed electrolysis. Detailed analysis results can be found in [link to analysis]. Figure 6 a-6d; wherein, the reduction potential of the pulse electrolysis is -0.6 to -2.4 vs. RHE, the electrolysis time is 30 to 70 s, the pulse potential is 0.6 V vs. RHE, and the electrolysis time is 5.0 s.
[0057] Depend on Figure 6 From a, we can know that pure Cu 2-x The C2 Faradaic efficiency (FE) of the Se catalyst under constant potential electrolysis conditions (optimal production potential -1.6V vs. RHE, at which the selectivity of C2 products is highest) is... C2 The figure is only 28.6%, which is due to the excessive number of unreacted electrons that will cause Cu to... + Reduced to Cu 0 This results in low selectivity for the C2 product.
[0058] Depend on Figure 6 b indicates that CQDs are used as storage pools in Cu 2-x After Se, the FE of the sample can be clearly observed. C2 Significantly improved, at an application potential of -1.6V vs. RHE, FE C2 The efficiency was increased to 45.5%, but it was still not ideal. This indicates that although the electron storage effect of CQDs can protect Cu... + However, excessive reducing electrolysis will still reduce the overflowing electrons to Cu. + Species.
[0059] Depend on Figure 6 c indicates that under pulsed potential electrolysis, Cu 2-x The selectivity for C2 products of Se can be increased to 45.5%. This may be due to the partial oxidation of Cu upon application of the oxidation potential. 0 Oxidized to Cu + This indicates that pulse electrolysis significantly contributes to performance improvement, but exhibits [specific FE content missing]. C2 It's not high.
[0060] Depend on Figure 6 d indicates that Cu 2-x Se / CQD exhibits the highest FE at -1.6V vs. RHE. C2 It reached 85.3%; compared with Figure 6 c of Cu 2-x Compared to Se, a significant improvement was achieved. This indicates that although pulse electrolysis contributes significantly to the performance improvement, the electronic storage effect of CQDs is indispensable. Furthermore, almost no CO formation was detected, indicating that the efficiency of CC coupling is much greater than the rate of CO formation; that is, the generated *CO is almost completely converted to C2 products via CC coupling. In addition, Cu... 2-x Even at extremely negative application potentials up to -2.4 V vs. RHE, no excessive occurrence of the hydrogen evolution reaction side reaction was observed in Se / CQD. More importantly, the selectivity for the C2 product remained as high as 77.4%. This indicates that Cu... 2-x Se / CQD can effectively protect Cu + High selectivity for C2 products can be achieved even at high overpotentials. Furthermore, under pulsed electrolysis conditions, Cu... 2-x Se / CQD exhibits an ultrawide C2 product potential window, up to 1.6V, and FE C2 >70%.
[0061] The above results demonstrate that CQDs, acting as electron storage cells coupled with pulsed electrolysis, play a crucial role in enhancing the performance of C2 products. Only by combining the electron storage effect of CQDs with pulsed potential electrolysis can the selectivity of C2 products be maximized. In other words, Cu... 2-x Se / CQD exhibits excellent selectivity in the electroreduction reaction of CO2 to generate C2 products.
[0062] In summary, the CQDs-modified Cu-based catalyst proposed in this application innovatively reduces the amount of unreacted electrons that could transfer Cu to the atmosphere. + Reduced to Cu 0 The occurrence of this process enhances the performance of the catalyst. Based on this, under pulsed potential electrolysis, CQDs-modified Cu-based catalysts overcome the technical problem of limited electron storage capacity of CQDs, fundamentally realizing the Cu… + Its long-term stability.
Claims
1. A highly stable CQDs-modified Cu-based catalyst, characterized in that: The modified copper-based catalyst consists of a copper-based catalyst and an appropriate amount of CQDs dispersed on the surface of the copper-based catalyst, wherein the weight ratio of the copper-based catalyst to the CQDs is 100:2-100:
20. The modified copper-based catalyst is prepared by the following method: CQDs and the raw materials for preparing the copper-based catalyst are added to a reaction apparatus, and the reaction is carried out using a hydrothermal synthesis method at 160-200℃ for 18-30 h. After the reaction is complete, the CQDs-modified Cu-based catalyst is obtained. The copper-based catalyst is Cu. 2-x Se.
2. The application of the CQDs-modified Cu-based catalyst as described in claim 1 in electrochemical reactions, characterized in that: The electrochemical reaction described is specifically a CO2 reduction reaction.
3. The application of the CQDs-modified Cu-based catalyst according to claim 2 in electrochemical reactions, characterized in that: The specific application is as an electrode used in electrochemical reactions.
4. A method for electrochemical reactions using the CQDs-modified Cu-based catalyst as described in claim 1, characterized in that: Electrochemical reactions were carried out using pulse electrolysis.
5. The method for electrochemical reaction using the CQDs-modified Cu-based catalyst according to claim 4, characterized in that: The pulsed electrolysis potential is 0.2~0.8 V vs. RHE, and the pulse duration is 2~10 s.
6. The method for electrochemical reaction using the CQDs-modified Cu-based catalyst according to claim 4 or 5, characterized in that: The electrochemical reaction described is the electrocatalytic reduction of CO2 to prepare C2 products.
Citation Information
Patent Citations
Carbon quantum dot / cuprous oxide compound (CQDs / Cu2O) as protein proteolysis catalyst and application thereof
CN107511151A
